Meningkatkan Hasil Belajar Pak Dengan Model Problem Based Learning Kelas VC SD Santo Markus II Jakarta Timur - Fransiska Binarayati; Hartutik Hartutik; Paulus Asriadi (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
This research is motivated by the lack of maximum student learning outcomes in Catholic Religious Education Learning Class VC SD Santo Markus II, East Jakarta. The Problem Based Learning Learning Model is designed to activate students in solving a problem. The purpose of this study is to measure the improvement of student achievement and the ability to think of students after applying the Poblem Based Learning Learning Model. This research method is Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of one meeting and four stages, namely planning, implementation, observation, reflection. The research subject consists of students of VC SD Santo Markus II, East Jakarta, totaling 24 people. Collection techniques in the form of observations, and tests. Indicators Observation Aspects of Creative Thinking Profile of Pancasila Students are a) Producing original ideas or ideas, b) having the ability to think creatively by clarifying and questioning many things, c) seeing something with a different perspective, d) applying new ideas according to the context and e) giving rise to various alternative solutions. The results of this study can be concluded that student learning outcomes in cycle 1 are obtained by 21% of proficient data, 21% capable, 50% feasible and 8% began to develop. Increases in cycle 2 which is the advanced stage of 58%, capable of 25%, feasible 17%and no one is starting to develop. The dimensions of students' creative thinking in cycle 1 obtained 0% data highly developed, 50% developed as expected, 33% began to develop and 17% were developing. Increasing in cycle 2. ie 54% greatly developed, 25% developed as expected, 21% began to develop and no one was in a developing stage. Thus it can be concluded that using the Problem Based Learning learning model can improve the aspects of Pancasila Student Profile and Student Cognitive Aspects in Catholic Religious Education Learning in Class VC SD Santo Markus II, East Jakarta.